Adverse drug event risk assessment by the virtual addition of COVID‐19 repurposed drugs to Medicare and commercially insured patients' drug regimens: A drug safety simulation study. Issue 5 (25th August 2021) - Smith, Matt K.; Bikmetov, Ravil; Al Rihani, Sweilem B.; Deodhar, Malavika; Hafermann, Matthew; Dow, Pamela; Turgeon, Jacques; Michaud, Veronique
Abstract: Drug safety is generally established from clinical trials, by pharmacovigilance programs and during observational phase IV safety studies according to drug intended or approved indications. The objective of this study was to estimate the risk of potential adverse drug events (ADEs) associated with drugs repurposed for coronavirus disease 2019 (COVID‐19) treatment in a large‐scale population. Drug claims were used to calculate a baseline medication risk score (MRS) indicative of ADE risk level. Fictitious claims of repurposed drugs were added, one at a time, to patients' drug regimens to calculate a new MRS and compute a level of risk. Drug claims data from enrollees with Regence health insurance were used and sub‐payer analyses were performed with Medicare and commercial insured groups. Simulated interventions were conducted with hydroxychloroquine and chloroquine, alone or combined with azithromycin, and lopinavir/ritonavir, along with terfenadine and fexofenadine as positive and negative controls for drug‐induced Long QT Syndrome (LQTS). There were 527, 471 subjects (56.6% women; mean [SD] age, 47 years [21]) were studied. The simulated addition of each repurposed drug caused an increased risk of ADEs (median MRS increased by two‐to‐seven points, p < 0.001). The increase in ADE risk was mainly driven by an increase in CYP450 drug interaction risk score and by drug‐induced LQTS risk score. The Medicare group presented a greater risk overall compared to the commercial group. All repurposed drugs were associated with an increased risk of ADEs. Our simulation strategy could be used as a blueprint to preemptively assess safety associated with future repurposed or new drugs.